Surviving the Titanic Disaster: Economic, Natural and Social Determinants - Bruno S. Frey; David A. Savage; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2009)
The sinking of the Titanic in April 1912 took the lives of 68 percent of the people aboard. Who survived? It was women and children who had a higher probability of being saved, not men. Likewise, people traveling in first class had a better chance of survival than those in second and third class. British passengers were more likely to perish than members of other nations. This extreme event represents a rare case of a well-documented life and death situation where social norms were enforced. This paper shows that economic analysis can account for human behavior in such situations.
Keywords: D63; D64; D71; D81; 330; Decision under Pressure; Tragic Events and Disasters; Survival; Quasi-Natural Experiment; Altruism